An Early Paleozoic orogenic gold belt along the Jiang−Shao Fault, South China: Evidence from fluid inclusions and Rb–Sr dating of quartz in the Huangshan and Pingshui deposits. (1st May 2015) - Ni, Pei; Wang, Guo-Guang; Chen, Hui; Xu, Ying-Feng; Guan, Shen-Jin; Pan, Jun-Yi; Li, Lin
Highlights: Gold orebodies are hosted in ductile shear zones of the Neoproterozoic strata. Extensive fluid immiscibility effectively promoted gold precipitation. Fluid inclusion Rb–Sr dating at Pingshui yielded an Early Paleozoic age. We identify an Early Paleozoic orogenic gold belt along Jiang–Shao zone, South China. Abstract: There are several gold deposits in the eastern section of the regional Jiang−Shao Fault between the Yangtze and Cathaysia Blocks in South China. Auriferous quartz veins in these deposits are strictly hosted in second-order NE-trending ductile shear zones. The ores generally contain low amounts of sulfide minerals (<5%), with pyrite as the most common sulfide mineral hosting native gold. Detailed fluid inclusion work and Rb–Sr dating were conducted on the auriferous quartz veins from the Pingshui and Huangshan deposits. H2 O–CO2 inclusions (type I) and aqueous inclusions (type II) ubiquitously coexist in the main mineralization stage veins in the Huangshan and Pingshui deposits. Type I and II inclusions in the Huangshan deposit have similar homogenization temperatures at 214–282 °C, but different salinities with 1.2–6.0 and 2.7–8.7 wt.% NaCl equivalent, respectively. In the gold orebodies from the Pingshui deposit, type I and II inclusions also have similar homogenization temperatures ranging from 236 to 304 °C, but different salinities ranging from 1.2 to 6.4 and from 3.2 to 9.8 wt.% NaCl equivalent, respectively. Fluid inclusion observations and microthermometric results show that the ore fluids are low salinity and CO2 -rich. Petrography and microthermometric results of fluid inclusions suggest that extensive fluid immiscibility occurred during the gold mineralization stage. Rb–Sr dating of quartz-hosted fluid inclusions (ca. 450 Ma) for the gold mineralization at Pingshui, combined with previous radiometric age data (ca. 397 Ma) of gold mineralization at Huangshan, suggest that the regional gold mineralization was formed in the Early Paleozoic. This study suggests that there is an Early Paleozoic orogenic gold belt in the eastern section of the Jiang−Shao Fault, formed in response to the coeval northward underthrusting of the Cathaysia Block beneath the Yangtze Block during the Caledonian Orogeny in South China.